This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: 3 s + 12 = A ( s + 4) + B (3) Starting with the highest power of s , we find the value of A and B . Since the only term multiplying s on the right is A , we must have the following result: A = 3 Using this value for A , we can quickly find B . 3 s + 12 = 3( s + 4) + B (3) = 3 s + 12 + B (3) or B = Now we take the inverse transform to obtain our final result. f ( t ) = ( t ) + 3 e 4 t cos(3 t ) u ( t ) N OTE : We multiply by u ( t ) as a reminder that we are uncertain of the value of f ( t ) for t < 0. Since ( t ) = 0 for t > 0, we need only multiply the second term by u ( t )....
View Full Document
This document was uploaded on 09/02/2010.
- Spring '12